A framework for faculty memory information system - Mokhtar, S.; Abu Bakar, Z.; Husin, W.H.W. (2008)
Many approaches have been developed which claim to guide organization to use their common or shared memory in more, efficient way. One of the approaches is realizing the organizational memory with the hell.) of information system, resulting the term Organizational Memory Information System (OMIS). This paper introduces an initial effort towards developing a framework for organizing and managing as well as decluttering the faculty's information and knowledge assets through OMIS. The management of the faculty and the lecturers (ire the target audience for the framework that also intends to improve knowledge sharing within the faculty level and perhaps later at the university level. The proposed framework namely called Faculty Memory Information System (FMIS) portrays the interaction between components that support the faculty's memory and the information system components that support the effort to captures and preserves the faculty's knowledge. This project is concern with the application of knowledge management in the university environment, highlighting on the bottom-up implementation approach which starts at the faculty level with a faculty memory information system and later upon successful endeavor may proceed to the university level to create a university memory information system.